Fault Detection Analysis in Electrical Components Using IR Thermography: Applications and Recommendations - Malik, Mochamad Irlan; Rabbika, Anes Inda; Yanti, Yanti; Hadiputranto, Rachmanto (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Electric power distribution to consumers requires periodic preventive maintenance, including thermal inspection of electrical components. An efficient maintenance strategy can save an industry from potential hazards and devastating losses. Therefore, monitoring the temperature of electrical components is crucial to prevent excessive heat that can lead to fires. This research aims to analyze the detection of electrical component damage in consumer distribution networks using IR Thermography for consumer electric network maintenance. The method involves capturing thermal images of targeted hotspots in various components within the consumer distribution substation. The observed components include transformer 2500 kVA connections, connections in the Low Voltage Main Distribution Panle (LVMDP), connections in the Capacitor Bank, and the Panel Change Over Switch (COS). The acquired data is then processed using Smart View software for analysis, categorization, and recommendations. The results reveal the highest temperatures recorded were 91.0°C in the transformer 2500 kVA, specifically in Phase R, and 71.8°C in the LVMDP panel, in Phase T. These findings indicate that the main causes of temperature rise are load imbalance in the transformer and connection failure in the breaker junction.